8151 The Genetic Etiology Is a Relevant Cause of Central Precocious Puberty - Machado Canton, Ana Pinheiro; Seraphim, Carlos Eduardo; Montenegro, Luciana Ribeiro; Krepsichi, Ana Cristina; Mendonca, Berenice Bilharinho; Latronico, Ana Claudia; Brito, Vinicius Nahime (Journal of the Endocrine Society, 2024)
Abstract Disclosure: A.P. Canton: None. C.E. Seraphim: None. L.R. Montenegro: None. A. Krepsichi: None. B.B. Mendonca: None. A. Latronico: None. V.N. Brito: None. Background: The etiology of central precocious puberty (CPP) has expanded with the identification of new genetic causes, including the monogenic deficiency of MKRN3 in familial cases. Objectives: To assess the prevalence of CPP causes and the predictors of genetic involvement in this phenotype. Methods: A single-center retrospective cohort study was performed for an etiological survey of patients with CPP. All patients had detailed medical history, deep phenotyping, and brain MRI. Patients with CPP and no pathological brain lesions, previously considered idiopathic forms, were submitted to genetic studies, mainly DNA sequencing studies, genomic microarray, and methylation analysis. Results: We assessed 270 patients (241 girls) with CPP; 50 (18.5%) patients had CPP-related brain lesions, whereas 220 (81.5%) patients had normal brain MRI. Of the latter, 174 (165 girls and 9 boys) were included for genetic studies. Genetic etiologies were identified in 22 patients (20 girls and 2 boys), indicating an overall frequency of genetic CPP of 12.6%, which was higher in boys (22.2%) than in girls (12.1%). The most common genetic defects were MKRN3, DLK1, and MECP2 loss-of-function mutations, followed by 14q32.2 imprinting defects (Temple syndrome). Univariate logistic regression identified positive family history (OR 3.3; 95%CI 1.3-8.3; p=0.01) and associated neurodevelopmental disorders (OR 4.1; 95%CI 1.3-13.5; p=0.02) as clinical predictors of genetic CPP. A novel algorithm for investigating the etiology of CPP was set up, including genetic studies guided by clinical parameters. Conclusion: Distinct genetic causes were identified in 12.6% of CPP patients previously classified as idiopathic, revealing the genetic etiology as a relevant cause of CPP in both sexes. Family history and neurodevelopmental disorders were identified as predictors of genetic CPP, recommending that both factors should be actively investigated in the CPP workup. A novel algorithm for investigating the etiology of CPP can be practice-changing for those who assist children with precocious puberty. Presentation: 6/2/2024